Diversity and Dynamics of Active Small Microbial Eukaryotes in the Anoxic Zone of a Freshwater Meromictic Lake (Pavin, France) - Lepère, Cécile; Domaizon, Isabelle; Hugoni, Mylène; Vellet, Agnès; Debroas, Didier (Frontiers in Microbiology, 2016)
Microbial eukaryotes play a crucial role in ecosystem functioning and oxygen is considered to be one of the strongest barriers against their local dispersal. However, diversity of microbial eukaryotes in freshwater habitats with oxygen gradients has previously received very little attention. We applied high-throughput sequencing (V4 region of the 18S rRNA gene) in conjunction with quantitative PCR (DNA and RNA) and fluorescent in situ hybridization analyses, to provide an unique spatio-temporal analysis of microbial eukaryotes diversity and potential activity in a meromictic freshwater lake (lake Pavin). This study revealed a high genetic diversity of unicellular eukaryotes in the permanent anoxic zone of lake Pavin and allowed the discrimination of active vs. inactive components. 42 % of the OTUs (Operational taxonomic Units) are exclusively present in the monimolimnion, where Alveolata (Ciliophora and Dinophyceae) and Fungi (Dikarya and Chytrids) are the most active phyla and are probably represented by species capable of anaerobic metabolism. Pigmented eukaryotes (Haptophyceae and Chlorophyceae) are also present and active in this zone, which opens up questions regarding their metabolism.